Journal of Optical and Fiber Communications Research - Bjarklev, Anders; Chowdhury, Dipak; Nakazawa, Masataka; Someda, Carlo; Majumdar, Arun K.; SpringerLink (Online service) (New York : Springer New York : Imprint: .)
This journal was discontinued by Springer at the end of 2010 and is no longer accepting submissions.
Keywords: Physics; Electrical engineering; Physics, general; Electrical Engineering